The Effect of Macroscopic and Microscopic Patterns of Stainless Steel Surface on the Efficiency of Dropwise Condensation and Precipitation (International Journal of Engineering Materials and Manufacture, 2021)
Atmospheric water generator (AWG) technologies are considered a potential new source of freshwater. Thermoelectric (TEC) dehumidifiers are one of this technology where it uses the Peltier effect to create a heat flux at the junction of two different materials. This device is well known for its thermoelectric cooling application, from as small as portable beverage coolers to as big as submarines. The problems of using this device are ice buildup and relatively low efficiency. If the surface of the material can be engineered in a way that the dropwise condensation, as well as precipitation from the cooling plate, is enhanced, it is possible to maximize the efficiency of TEC-driven AWG with minimum energy consumption. This study investigates the effects of macroscopic (bump/dent, patterns that are visible to the human eye) and microscopic patterns (surface finish, quality, grain distribution, etc. visible under a microscope) on industry-grade stainless (SS) surfaces on dropwise condensation and precipitation. The surface contact angle is considered here to understand the hydrophobic/hydrophilic properties of the surfaces before and after applying hydrophobic coating under constant ambient conditions. Better droplet nucleation and quicker precipitation have been observed on the surfaces after treating a hydrophilic and hydrophobic surface with hydrophobic spray. It can be inferred that even though the initial surface property of the two samples were different, it was possible to achieve similar level of super hydrophobicity after applying the spray. This proves that surfaces can be modified with appropriate treatment to achieve desired properties.